Anodic stripping voltammetry of silver in the absence of electrolytes: Theory and experiment - Ngamchuea, K; Batchelor-Mcauley, C; Compton, R (Elsevier, 2018)
This work demonstrates that anodic stripping voltammetry at a microdisc electrode allows the detection of silver in the absence of added supporting electrolyte. The voltammetry however becomes distorted under low-support conditions. A semi-analytical model is developed to investigate the effects of the lack of supporting electrolyte on the voltammetric responses. First, the alteration in the double-layer kinetics is studied. In particular, we show that the classical Frumkin correction cannot explain the distorted shape of the voltammetry and only accounts for no more than ~50% of the shift in the voltammetric peaks. Second, compared to the Frumkin correction, Ohmic drop contributes much more significantly to the shift in the peak potential and the distorted wave shape upon lowering electrolyte concentrations. The Ohmic drop determined on the basis of predicted constriction resistance as expressed by Newman gives a reasonable approximation to the solution resistances, especially at ionic strengths above 200 μM. In deionized water or ultra-low conductivity water with the ionic strength of sub-micromolar level, a discrepancy in the resistances of up to a factor of 25 was observed. This discrepancy likely arises due to the assumptions made in applying the Newman model to the experimental system. Finally, we show that a model which considers simultaneously the electrode kinetics and the ohmic drop effects give a consistent fit with experimental data, when the values of the resistances are appropriately adjusted to account for the inaccuracy in the approximation of constriction resistances.